The Amendment Deed to Foundation Budget through Notary on Foundation's Assets from Waqf Process - Anis Safitri; Gunarto Gunarto (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The establishment of a Foundation after the enactment of Law Number 28 of 2004 concerning Amendments to Law of the Republic of Indonesia Number 16 of 2001 concerning Foundations is carried out with the condition that there are founders, a Notary Deed and obtain legal entity status which after the deed of establishment obtains approval from the Minister of Justice and Human Rights or appointed officials. Along the way, the foundation can also experience changes. Amendments may include amendments to the articles of association, except for the purposes and objectives. The purpose of this journal research is one, to analyze the legal review of the position of the deed of amendment to the foundation's articles of association through a notary on the foundation's assets from the waqf process. two, to analyze the obstacles and solutions for changing the foundation's articles of association through a notary on the foundation's assets from the waqf process. The approach method in this legal journal research is to use normative legal research with a sociological juridical approach and other approaches including case approach, statute approach, historical approach, comparative approach, Conceptual approach (conceptual approach) . the results of this study indicate the obstacles and solutions for changing the foundation's articles of association through a notary on the foundation's assets from the waqf process is a legal consequence of the notary's error in making a deed of amendment to the articles of association with the intention of adjusting the foundation's articles of association with the foundation law, if any parties who feel aggrieved and there are those who file a notary lawsuit can be sued to pay compensation, interest and fees. And the notarial deed has no legal force if it is not in accordance with the laws and regulations that apply to the foundation.